Scientific tools for forming professional competence of patrol police officers - Ivan Okhrimenko; Andrii Antoshchuk; Alla Marchuk; Valentyn Bondarenko; Vadym Piaskovskyi (International Journal of Evaluation and Research in Education (IJERE), 2022)
In this paper, the scientific sources analysis was presented. The peculiarities of the professional competence formation of the future patrol officers were determined. Moreover, the specifics of the service activity of patrol officers were considered. The original method for the formation of professional competence of modern police officers was substantiated and tested its effectiveness. The essence of this methodology was to introduce simulated situational tasks, aimed at forming the professional skills and abilities of future police officers. The pedagogical experiment involved students of the primary vocational training course applied in 2018 (n=183) who were studying at the center of primary vocational training “Police Academy” of the National Academy of Internal Affairs (Kyiv, Ukraine). An experimental (EG, n=93) and control (CG, n=90) group were formed. Cognitive and operational criteria evaluated the efficiency of the original methodology. The results of the pedagogical experiment indicated the greater efficiency of the original methods compared to the traditional one. A significant (р<0.05-0.001) improvement of the indicators “Knowledge of professional and practical course”, “Professional and practical skills formation” and “The effectiveness of solving scenarios” was designated.